The flag effect on the physical performance of soccer assistant referees - Gottlieb, Roni; Aviv, Efi; Shalom, Asaf; Calleja Gonzalez, Julio; Meckel, Yoav (Edelweiss Applied Science and Technology, 2024)
The aim of the study is to compere the performance of the assistant referee without and with the flag, based on existing and novel tests. Introduction: Millions of fans around the world are invested in the game of soccer, cheering on their favorite team, practicing their skills in the park, or simply watching from afar via the media. As such, fairness in refereeing is of the utmost importance, regardless of the level of game or the teams who are playing. The refereeing team plays a critical role in enforcing the rules of the game and ensuring fair play on the field. In addition to working together in the utmost coordination, the referee, two assistant referees, and the standby official are required to oversee the entire match, while making crucial decisions in split seconds. In addition to their verbal communications, assistant referees must carry and use their flag throughout the game, as means for signally their decisions. When running along the sideline, assistant referees hold the flag in opposite hand to the direction in which they’re moving at that time – resulting in up to 30% of their movements during the game being sideways movements. Testing and comparing the athletic abilities of assistant referees is therefore an essential component in ensuring the accuracy and fairness of soccer matches. Assistant referees play a critical role in enforcing the rules of the game, and their ability to run quickly and accurately while holding a flag can have a significant impact on the outcome of the performance. Participants: 18 assistant referees (two female) who are on the staff of the National League in the Israel Soccer Association. The participants’ mean (±SD) variables were as follows: age=29yrs (±3.4); height=178cm (±0.06); weight=68.22kg (±10.45); fat percent=14.67% (±4.86); and seniority on the league=3.11yrs (±1.45). Results: Show that in all the tests the performance was significant better without the flag (RST, agility test and linear speed), the performance decrement % (RST), show no significant result, P<0.05, t (0.91) = 17. Conclusions: the referee run faster without the flags but the no deferent in the fatigue, so they have to train and testing with flags like in the game.